The way things work. Ballooning [videorecording (DVD)] - Zamora, Diego; Macaulay, David (Schlessinger Media, 2003)
Some of the Mammoth Islanders decide to explore the far side of a distant mountain ridge on a breezy spring day. Halfway up the steep trail, they become trapped and must be rescued by a hot air balloon.